Temporal dynamics of maintenance in young and old adults. Issue 1 (30th April 2018) - Fanuel, Lison; Plancher, Gaën; Monsaingeon, Noé; Tillmann, Barbara; Portrat, Sophie
Abstract: The present study investigated the time course of refreshing in young and old adults by analyzing the influence of memory load on response times for the processing of concurrent information. One to five squares sequentially displayed in random locations had to be memorized. Before the serial recall of the squares' locations, participants performed self‐paced parity judgments on sequentially presented numbers. Trials without squares—not requiring memorization, but only parity judgments—constituted the control condition. Response times of parity judgments were separated for responses to the first digit and for responses to subsequent digits. In young adults, the results provided evidence for consolidation and refreshing, namely, the linear increase of first and subsequent response times with memory load. For old adults, a different pattern emerged: (1) the mean response time for the first digit processing was longer with memorization than without, probably reflecting task‐switching rather than consolidation; and (2) in contrast to young adults, memory load did not affect subsequent response times, suggesting a deficit in the initiation of refreshing. Overall, findings support the hypothesis of impaired refreshing in aging.